The psychology and dynamics behind social media interactions - Desjarlais, Malinda, 1980- (Advances in psychology, mental health, and behavioral studies., 2020)
"This book summarizes, synthesizes, and critiques current social media research in order to provide insight into the benefits and detriments of social media through the lens of psychological theories"--